Analysis of Implementation of Kurikulum Merdeka in English Learning Process at SMA Negeri 1 Palembayan - Muthianiva Aulia Sukma; Edi Trisno (Universitas Negeri Padang, 2023)
This research analyzed the implementation of Kurikulum in the learning process of English subjects at SMA Negeri 1 Palembayan. This research is focused on the implementation of Kurikulum Merdeka in the differentiated learning process in English subjects at SMA Negeri 1 Palembayan. The design of this research is descriptive research. Indicators of this research were devided into three categories based on Tomlinson (2001), three important aspect of student learning needs in differentiated learning are readiness to learn, interest in learning and student learning profile. The data were collected by using interview. The participants of this reserach were English teachers at SMA Negeri 1 Palembayan. The result of this research showed that the implementation of the Kurikulum Merdeka in the first year at SMA Negeri 1 Palembayan was quite good. Teachers use a variety of media, guidance that suits students' learning styles and different assignments according to students' abilities. This method is applied to meet student needs in three categories, namely readiness to learn, interest in learning and student learning profile. From the results of this research, it can be concluded that the implementation of the Kurikulum Merdeka in the differentiated learning process in English subjects at SMA Negeri 1 Palembayan is quite good in meeting students' needs for readiness to learn, interest in learning and student learning profile.Keywords: Kurikulum Merdeka, differentiated learning.